THE GLORY OF A TEACHER IN THE PERSPECTIVE OF IMAM AL-GHAZALI - Annisa Darma Yanti; Ellya Roza; Eva Dewi; Mohamad Aso Samsudin (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
The condition of Indonesian society lately is very complex in the field of education so that there are many brawls between students, undisciplined, dishonest, lazy, various bad behaviors that appear among the younger generation, plus low achievement, creativity and innovation. On the other hand, the very tough future challenges require this nation to remain enthusiastic, while being able to compete better in this global era. In this case, the role of the teacher is indispensable as a person in charge of educating and teaching in various scientific aspects. This research is a type of library research. What is called library research or often also called library studies, is a series of activities using library data collection methods, reading and recording and processing research materials. This research uses a qualitative approach to describe the problems and research focus. After the researcher collects a number of data related to the theme and discussion in this study, the researcher immediately starts the message of analyzing the data. The analysis technique used is the Content Analysis and Descriptive Analytic method. In this process, the first thing to do is classify the data. The teacher according to Imam al-Ghazali is someone who works to perfect, purify and purify and guide his students to get closer to God. He also said that from one point of view, teaching knowledge is an act of worship to Allah Ta'ala and from another point of view it is the duty of man to be the khalifah of Allah. In doing so, he has become the most honorable of the khalifs of Allah.